Improving Islamic Financial Literacy of Students of PPMTI Tanjung Berulak through a Participatory Education Program Based on Counseling - Mifta Hasda; Saru Reza; Hidayat Hidayat; Zubaidah Assyifa; Muhammad Arif (Journal of Community Service and Empowerment, 2026)
This community service activity was carried out at the Madrasah Tarbiyah Islamiah Islamic Boarding School (PPMTI) Tanjung Berulak with the theme "Introduction to Sharia Finance as a Solution for Islamic Financial Management through a Participatory Education Program Based on Counseling." This program aims to increase students' understanding and awareness of the concepts and practices of sharia financial management as an alternative financial management in accordance with Islamic principles. The activity is designed to equip students not only with normative Islamic knowledge, but also with the application skills in applying sharia financial principles, particularly through an introduction to the systems and products of sharia financial institutions such as Sharia Banks. The activity stages began with preparation that included coordination with the boarding school management, preparation of educational materials, and development of supporting media in the form of presentation materials. The activity was attended by grade XII students with a participatory counseling approach through interactive lectures, discussions, and questions and answers. This approach provides space for students to actively participate, explore understanding, and relate the material to the context of everyday life. The results of the activity demonstrate an increased understanding among students of the urgency of Islamic financial management, as well as a growing interest and enthusiasm for implementing Islamic financial principles in their personal and social lives. This program is expected to encourage students to become agents of Islamic financial literacy in their communities, supporting the creation of an Islamic and sustainable society.